Teachers’ Motivation and Job Effectiveness in Public Senior Secondary Schools in Edo State, Nigeria - Imarhiagbe, Margaret Enore; Idahosa-Erhabor, Abieyuwa (NIU Journal of Educational Research, 2025)
This study examined teachers’ motivation and their job effectiveness in public senior secondary schools in Edo State. The research design adopted was a descriptive survey. Three (3) research questions were raised. The population of the study comprised 309 school principals and 6180 teachers from the 309 public senior secondary schools in the state. The sample size was 31 principals and 309 teachers representing 10% and 5% respectively. A multi-stage sampling technique was adopted to select the sample size, Data was analyzed, using Mean and standard Deviation to answer research questions 1 and 2, and Pearson Product Moment Correlation Coefficient (r) was used to answer question 3. The findings revealed that the teachers were motivated to a high extent; their job performance level was high and there was a positive correlation between teachers’ motivation and their job effectiveness in public senior secondary schools in Edo State. It was therefore recommended that Edo State Government should continue to motivate its teachers by sustaining and improving on the incentives given to them. Keywords : Teacher, motivation, job, effectiveness, salary, professional development, facilities.